Diagnosis of induction motor stator faults around rotor slot harmonics using the Matrix Pencil method - Mohamed Kouadria; Zakaria Chedjara; Chun-Lien Su; Mohamed Benbouzid; Josep M. Guerrero; Babul Salam KSM Kader Ibrahim; Hafiz Ahmed (Results in Engineering)
To improve the monitoring and diagnosis of stator faults at their early stages in induction motors, several methods have been developed, particularly parametric methods. This article thus proposes a new approach based on the Matrix Pencil method for high-resolution spectral analysis. This method aims to avoid the limitations of the classical method based on power spectral density estimation using the periodogram. Indeed, the proposed approach offers very high frequency resolution even for very short acquisition times, thus allowing improved detection even for low amplitudes. Furthermore, to optimize the calculation time of this method, the article suggests focusing the analysis only on the frequency band corresponding to the first rotor slot harmonics. This approach aims to avoid any interference with the frequency signatures of external factors, which are generally present at very low frequencies. The results obtained from simulation and experimental tests demonstrate the effectiveness and reliability of this new approach for detecting inter turns short-circuit faults in stator windings of the induction motor.